Construction of Cultural Resilience through the Exploration of Agrarian Ritual Meanings in Kemiren Banyuwangi Village - Muhammad Bahaudin Maulidi; Ahimsyah Yunita Anwar; Fericka Ardhita Putri Santoso; Risa Aminatus Sholikha; Mara Qonitatillah; Fitrah Yasmin Bakhitah; Ali Imron (Universitas Muhammadiyah Ponorogo, 2026)
This research aims to analyse the symbolic meaning of agrarian rituals in Kemiren Village, Banyuwangi, and its relationship with cultural resilience. Using a phenomenological approach, this research explores the perspectives of local actors in cultural, historical and social contexts. Data were collected through observations, interviews and documentation studies to understand the agricultural ritual tradition and its role in cultural preservation. The results showed that agrarian rituals have philosophical meanings that strengthen community identity as well as human relationships with nature. This ritual is also an intergenerational tool in preserving ancestral culture. The results of this study confirm the need for collaboration between the government and local communities in supporting cultural preservation through the promotion of culture-based tourism by utilising information technology. However, this research is limited to one agricultural area in the cultural heritage of Kemiren Village, so further research is needed to study more widely in other agricultural areas to obtain unique data and facts from various actors preserving agrarian rituals. As well as to encourage the development of science, future research is needed on the possibility of food security ideas contained in the customs of the ancestors, in this case agrarian ritual processions.